Argentina ID Case Study : The Evolution of Identification - World Bank (World Bank, Washington, DC, 2020)
As the birth place of fingerprint identification and one of the first countries in Latin America to establish a civil registry (CR), Argentina has a long history of identification. Until 2009, however, its civil registration and national ID systems suffered from a number of issues, including noninteroperable civil registries, between provinces, lack of integration between CR and ID systems, and slow and inefficient paper-based processes. Since 2009, however, Argentina has made great efforts to steadily enroll more than 45 million residents to establish a robust national digital ID system. Birth registration is now universal and 98 percent of the population is in possession of a national ID card, including more than two million migrants. The national ID agency, RENAPER (Registro Nacional de las Personas), responded to more than 230 million queries in 2018 from the public and private sector creating the foundation for a digital economy. Since 2009, in the context of a federal country with autonomous provinces working together with the federal government, with the support of the Ministry of Modernization, have implemented a series of innovative initiatives to create a digital one - stop shop called Mi Argentina, such as digital birth and death registration, verifying "proof of life" of pension beneficiaries remotely, and offering verification services to public and private institutions. This was achieved through political commitment at the federal and local levels sustained over 10 years, public investment and legislative reforms on civil registration, identification, and data protection, and personal data privacy.